Evaluation of combined cytotoxic effects of effects of ochratoxin A and fumonisina B1 in human liver and renal cells - Tavares, A.M. (2015)
Mycotoxins are fungal food contaminants with potential to cause severe acute and chronic conditions1. Therefore, food contamination with mycotoxins such as ochratoxin A (OTA) and fumonisin B1 (FB1) causes great concern. Previous studies addressed the co-occurrence of these toxins in foods2, however there is little knowledge on their combined cytotoxic effects. In the present study we aimed to evaluate the cytotoxic effects of mixtures of OTA and FB1 in two human-derived cell lines.